The Empirical Study of Technology Acceptance Model among Mobile Banking Users in Indonesia - Palumian, Yonathan; Tarigan, Zeplin Jiwa Husada; Garvey, Fransiscus Solanus Rayhan; Sundari, Santi (Journal of Ecohumanism, 2024)
Mobile banking is an innovation of banking services developed to facilitate the activities and financial transactions of customers. Mobile banking offers a high degree of ease and flexibility so it can be used anywhere and anytime through the practices of each user. The continued use of mobile banking is influenced by several important factors including expectation-confirmation, satisfaction, and perceived usefulness. The study aims to test the role of the above three factors in their influence on sustainable intentions among mobile banking users in Indonesia. The explanatory research with this quantitative approach involved 326 respondents in an online questionnaire-based survey. Using partial least square (PLS-SEM) as the data analysis technique, this study explains that perceived usefulness and satisfaction have a significant influence on continuous usage intention while expectation-confirmation has no significant effect on the continuous intention.